ADATs: roles in tRNA editing and relevance to disease - Mao Xue-Ling; Eriani Gilbert; Zhou Xiao-Long (Acta Biochimica et Biophysica Sinica)
Transfer RNAs (tRNAs) play central roles in protein biosynthesis. Post-transcriptional RNA modifications affect tRNA function and stability. Among these modifications, RNA editing is a widespread RNA modification in three domains of life. Proteins of the adenosine deaminase acting on tRNA (ADAT) family were discovered more than 20 years ago. They catalyze the deamination of adenosine to inosine (A-to-I) or cytidine to uridine (C-to-U) during tRNA maturation. The most studied example is the TadA- or ADAT2/3-mediated A-to-I conversion of the tRNA wobble position in the anticodon of prokaryotic or eukaryotic tRNAs, respectively. This review provides detailed information on A-to-I and C-to-U editing of tRNAs in different domains of life, presents recent new findings on ADATs for DNA editing, and finally comments on the association of mutations in the ADAT3 gene with intellectual disability.